USM, NCBE SIGN MoU TO ENHANCE EDUCATIONAL COOPERATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, January 2017 Universiti Sains Malaysia (USM) and Nagoya City Board of Education (NCBE) today signed a Memorandum of Understanding (MoU) to enhance cooperation in the education field.